18.0k views
0 votes
How do I solve this?

-6x-1+5x^2 = 8x^2

Thanks

1 Answer

6 votes

Answer:


\displaystyle x=(-3+√(6))/(3)\text{ and } x=(-3-√(6))/(3)

Or, by approximating:


x\approx-0.1835\text{ or } x\approx -1.8165

Explanation:

Let’s convert this to standard form. We have:


-6x-1+5x^2=8x^2

Subtract 5x² from both sides:


-6x-1=3x^2

And add 6x and 1 to both sides:


0=3x^2+6x+1

This is not factorable. So, we will need to use the quadratic formula.

The quadratic formula for a quadratic in standard form is given by:


\displaystyle x=(-b\pm√(b^2-4ac))/(2a)}

In this case, a=3; b=6, and c=1.

Substitute appropriately:


\displaystyle x=(-6\pm√(6^2-4(3)(1)))/(2(3))

Simplify:


\displaystyle x=(-6\pm√(24))/(6)

We can simplify the square root:


√(24)=√(4)\cdot√(6)=2√(6)

Hence:


\displaystyle x=(-6\pm2√(4))/(6)

Simplify:


\displaystyle x=(-3\pm√(6))/(3)

Hence, we will have two solutions:


\displaystyle x=(-3+√(6))/(3)\text{ and } x=(-3-√(6))/(3)

Approximating them, we can see that our solutions are approximately:


x\approx-0.1835\text{ or } x\approx -1.8165

User EComEvo
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.